Imposter Syndrome Among First-Generation HBCU Social Work and Health Science Students. - Stanley, Lauren H. K.; Morrison, Cleopatra; Roberts, Dontaè; Bates, Douglas (Journal of Social Work Education)
First-generation college students (FGCS) are more likely to face institutional barriers to education, as many maintain identity status(es) in vulnerable or intersecting oppressed groups, such as race, class, or gender. FGCS status places students at risk of experiencing increased chronic feelings of inferiority and self-doubt, common feelings of imposter syndrome (IS), during their academic career. Given the overrepresentation of FGCS attending historically Black colleges and universities (HBCUs), there is a strong likelihood that many students may be experiencing feelings of IS. Yet there is limited empirical evidence of associations between FGCS and IS in HBCU Bachelor of Social Work (BSW) students. The current study applied an HBCU-student success framework to social work and health sciences students (N=62) at an HBCU to model how student characteristics, learning contexts, and internalized statuses related to feelings of IS. Hierarchical regression results supported the high prevalence of IS feelings in FGCS and demonstrated the protective effect of an HBCU environment. The comprehensive model of HBCU-student success explained 32.4% variance with statistically significant main effects of student race predicting lower IS scores and FGCS status predicting higher IS scores. Identity statuses are important considerations for BSW student well-being at HBCUs.